BRAND IMAGE ENHANCEMENT: Analysis of the Inspirational Class Program at State Senior High School 2, Pasuruan - Elif Nur Hubbi Fitriya; Isroqunnajah; Parmujianto (Kopertais Wilayah III Yogyakarta, 2026)
The intensifying competition among educational institutions necessitates that madrasahs move beyond conventional academic services to establish a strong and distinctive institutional brand image. This study analyzes: (1) the implementation of the Inspirational Class Program in enhancing the brand image of MAN 2 Pasuruan; (2) the challenges encountered during program implementation; and (3) the program’s impact on strengthening brand image and stakeholder trust. A descriptive qualitative approach utilizing field research was employed. Data collection methods included participatory observation, in-depth interviews, and document analysis. The findings demonstrate that the Inspirational Class Program—comprising Tahfidz, Literacy, Bilingual, Fashion, and Digital classes—is systematically managed through Planning, implementation, and evaluation. The program effectively enhances the madrasah’s brand image in multiple dimensions by simultaneously cultivating religious, intellectual, global, creative, and modern identities. Key constraints include uneven human resource competencies, budget limitations, and infrastructure gaps. This study advances Islamic education marketing management by highlighting program innovation strategies as tools for institutional branding. Keywords: Madrasah Brand Image, Inspirational Class Program, Islamic Education Management, Learning Innovation, MAN 2 Pasuru